Impact of Energy consumption and Economic Growth on Environmental Performance: Implications for Green Policy Practitioners - AlZgool, Mahmoud Radwan Hussein; Shah, Syed Mir Muhammad; Ahmed, Umair (International Journal of Energy Economics and Policy, 2020)
Different approaches are required to forward evidence for green policy practitioners to make decision about employee, organizations and future course of actions to improve environmental performance. In this study, we analyzed the Environmental Kuznets Curve (EKC) hypothesis in the context of Bahrain in the presence of financial development. For this purpose, this study developed the quadratic model where carbon emission depends on economic growth (GDP), a square of economic growth (GDP2) and supporting variables are energy consumption, financial growth and trade Liberalization. For this purpose, using the annual time series data of Bahrain from 1980 to 2018 taken from the World Bank database. The Autoregressive distributive lag (ARDL) approach has been used. The results indicate that the EKC hypothesis is valid for the case of Bahrain because the positive relationship exists between economic growth and carbon emission and a square of economic growth poses a negative effect on carbon emission. While energy consumption is the primary source of boosting the carbon emission level. Both the short and long-run estimates confirm that there exists a positive relationship between economic growth and financial development and also energy consumption boosts carbon emission in Bahrain. Keywords: Energy Consumption, Financial Development, Trade, Carbon Emission, EKC Hypothesis JEL Classifications: N7, B26 DOI: https://doi.org/10.32479/ijeep.10222